Analysis of the Influence of Social Media Marketing on Purchase Intentions in @_Florie Products - Alifia Widya Ghaissani; Sheren Nadia; Pawitan, Gandhi (Program Sarjana Manajemen Universitas Internasional Batam, 2024)
This study investigates the impact of social media marketing on consumer purchase intention for the Instagram-based florist business, @_Florie. The research aims to understand the relationship between social media marketing strategies and purchase intention among Instagram users. The population consists of Instagram users who follow @_Florie, and the sampling technique used is purposive sampling. Data collection was conducted through questionnaires and observations. Quantitative methods were employed to analyze the data, including validity, reliability, simultaneous testing, and partial testing. Key findings indicate that dimensions such as entertainment, customization, electronic word-of-mouth (EWOM), interaction, and trendiness significantly influence purchase intention. The study concludes that effective social media marketing strategies can enhance consumer engagement and drive purchase intentions for online businesses.